Donation system using mobile application / Nur Fariza Zulaika Sabri - Nur Fariza Zulaika, Sabri (2016)
Fake donation is one of the main reasons why people become hesitate to give donation. Other than that, there are no specified donation application that lists the list of needy people and their details to give confidence for people to donate. In the other side, usage of mobile phone nowadays increased from times to times. In order to make the usage of mobile phone become beneficial, an application is invented. Donation system using mobile application is an application that may satisfies the both issues mentioned. List of receiver and their details is one of the elements that provided in the Donation System using Mobile Application. The donation gave by the donor also will be recorded to ensure the receiver know the total donation they received.